Pkm Program Kemitraan Bagi Guru Dalam Meningkatkan Kemampuan Pembelajaran Berbasis Karakter Kearifan Lokal Di Paud Danica Kids School Tamalanrea Makassar - Juanda Juanda (Politeknik Bina Madani, 2021)
Partners of this Community Partnership Program (PKM) are UKM with Danica Kids school teacher in Tamalanrea District, Makassar. The problem is that Kids school teachers have not been skilled in designing learning to shape children's character based on children's literature that has the character of local wisdom in designing assessment tools and child development based on Multiple Intelligences. This service aims to help Kids school teachers skillfully design learning to shape children's character based on local wisdom and design assessment tools for child development based on Multiple Intelligences. The method used is training in designing learning materials based on children's literature for the formation of early childhood characters based on local wisdom and workshops on assisting the implementation of Multiple Intelligences-based child development assessments. Activities carried out in the form of Tutorials, Workshops, Simulations, Implementation, and Mentoring. This PKM partnered with a Danica Kids school teacher in Tamalanrea District, Makassar. The target that has been achieved is that teachers are skilled in designing children's literature-based learning tools for early childhood character building based on local wisdom and then implementing them for children and assessments of child development based on Multiple Intelligences to measure children's development as a whole and integrated.